2015
DOI: 10.1002/adfm.201404535
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable, Biocompatible, and Flexible Organic Field‐Effect Transistors and Their Application in Temperature Sensing Arrays for Artificial Skin

Abstract: Application of degradable organic electronics based on biomaterials, such as polylactic‐co‐glycolic acid and polylactide (PLA), is severely limited by their low thermal stability. Here, a highly thermally stable organic transistor is demonstrated by applying a three‐arm stereocomplex PLA (tascPLA) as dielectric and substrate materials. The resulting flexible transistors are stable up to 200 °C, while devices based on traditional PLA are damaged at 100 °C. Furthermore, charge‐ trapping effect induced by polar g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
156
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(158 citation statements)
references
References 41 publications
1
156
0
1
Order By: Relevance
“…Some groups have reported fl exible and stretchable temperature sensors based on Si, [ 88 ] Si diodes, [ 5,65 ] organic diodes, [ 48 ] colorimetric temperature indicators, [ 87 ] and polar groups of dielectric-induced charge-trapping. [ 19 ] Kim et al [ 65 ] and Webb et al [ 5 ] fabricated a Si diode (PIN) based on a fl exible and stretchable temperature sensor array for wound healing and skin-temperature monitoring. Someya et al [ 48 ] demonstrated a temperature-sensor array based on a fl exible organic thin-fi lm transistor (OTFT) for e-skin application.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some groups have reported fl exible and stretchable temperature sensors based on Si, [ 88 ] Si diodes, [ 5,65 ] organic diodes, [ 48 ] colorimetric temperature indicators, [ 87 ] and polar groups of dielectric-induced charge-trapping. [ 19 ] Kim et al [ 65 ] and Webb et al [ 5 ] fabricated a Si diode (PIN) based on a fl exible and stretchable temperature sensor array for wound healing and skin-temperature monitoring. Someya et al [ 48 ] demonstrated a temperature-sensor array based on a fl exible organic thin-fi lm transistor (OTFT) for e-skin application.…”
Section: Reviewmentioning
confidence: 99%
“…These sensor arrays can be also used to monitor the wound-healing process, cancer screening, core-body-temperature assessments, and other types of clinical procedures. Also, Wu et al [ 19 ] developed a fl exible temperaturesensing array based on an OFET for application as artifi cial skin. By applying a three-arm stereocomplex poly(lactic-co -glycolic acid), the PLA (tascPLA) served as the gate dielectric in an OFET.…”
Section: Reviewmentioning
confidence: 99%
“…Besides, silicon (Si) nanoribbon and Si diodes [151], thermochromic liquid crystals [152], and three-arm stereocomplex polylactide based organic FETs [153], have been used for the fabrication of flexible temperature sensors.…”
Section: Flexible Temperature Sensorsmentioning
confidence: 99%
“…Polylactic acid (PLA) is a commonly used biodegradable plastic material (Tokiwa et al 2009;Vanstrom 2012) with good biocompatibility, gloss, transparency, thermal stability, and other characteristics (Cui et al 2007;Jung 2008;Wu et al 2015). Therefore, the application of this biofriendly material has grown extensively (Zhao and Gu 2014).…”
Section: Introductionmentioning
confidence: 99%